Differences of stimulated and unstimulated salivary flow rates in patients with dry mouth. Issue 1 (January 2015) - Hayashida, Jun-Nosuke; Minami, Sakae; Moriyama, Masafumi; Toyoshima, Takeshi; Shinozaki, Shouichi; Tanaka, Akihiko; Maehara, Takashi; Nakamura, Seiji
Abstract Purpose The purpose of this study was to clarify the usefulness of noninvasive examination items such as sialometry and Visual Analog Scale (VAS) in distinguishing Sjögren's syndrome (SS) in dry mouth patients from neurogenic/neuropsychiatric disorders and drugs (DND). Patients and methods The study cohort comprised 50 patients with SS and 28 patients with DND. The gum test and Saxon test for stimulated salivary flow rate (SSFR), the spitting test for unstimulated salivary flow rate (USFR) and VAS were performed in all the patients with dry mouth. Results In SS patients, the SSFR (mean: gum test, 6.34 mL/10 min; Saxon test, 1.19 g/2 min) and USFR (0.61 mL/15 min) were decreased. In DND patients, the SSFR (gum test, 16.35 mL/10 min; Saxon test, 3.58 g/2 min) was within the normal range, but the USFR (0.90 mL/15 min) was decreased. In VAS, SS patients scored significantly higher in the items of "water-drinking at meals", "difficulty in swallowing", and "taste abnormality", while significantly lower in the item of "oral pain". Conclusion These results suggest that the SSFR, USFR and VAS could be useful in distinguishing DND from SS.